Development of Android-Based Matematika Pintar Application to Mathematics Learning - Fakhri Auliya, Nanang Nabhar; Fakhriyana, Dina; Roza, Muhammad Yusron; Syawala, Azra Nur (Jurnal Pendidikan Matematika, 2022)
There needs to be a mathematics learning media that is in accordance with the times, so that it can motivate students to learn. This study aims to determine the development and feasibility of the Matematika Pintar application to mathematics learning for class VII. The application was created with the help of Adobe Flash CS6 software. The research method used is Research and Development (R&D) with the ADDIE model. The results of this study are: (1) Matematika Pintar contains all class VII material and has received suggestions from material experts, media experts, and users, (2) the feasibility results are based on the feasibility test of 2 material experts with a questionnaire instrument related to the aspects of completeness and accuracy of material who get an average score of 91.5, 2 media experts with a questionnaire instrument related to aspects of the view and presentation of the application get an average score of 74, users on a small-scale test as many as 6 people with a questionnaire instrument related to aspects of motivation, facilities, attraction, and benefits who get an average score of 83.667, and users in the main product field test as many as 30 people with a questionnaire instrument related to aspects of motivation, facilities, attraction, and benefits who get an average score of 81.8. The indicator used is if the average score>83.994 belongs to the very feasible category and 67.998 < average score ≤ 83.994 belongs to the feasible category. Perlu adanya media pembelajaran matematika yang sesuai dengan perkembangan zaman, sehingga dapat memotivasi siswa untuk belajar. Penelitian ini bertujuan untuk mengetahui pengembangan dan kelayakan aplikasi Matematika Pintar berbasis android untuk pembelajaran matematika kelas VII. Aplikasi dibuat dengan bantuan software Adobe Flash CS6. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model ADDIE. Hasil dari penelitian ini adalah: (1) aplikasi Matematika Pintar memuat semua materi kelas VII dan telah mendapatkan saran dan masukan dari ahli materi, ahli media, dan pengguna; (2) hasil kelayakan didasarkan pada uji kelayakan dari 2 orang ahli materi dengan instrumen angket terkait aspek kelengkapan dan keakuratan materi yang mendapatkan skor rerata sebesar 91,5, 2 orang ahli media dengan instrumen angket terkait aspek tampilan dan penyajian aplikasi yang mendapatkan skor rerata sebesar 74, pengguna pada uji skala kecil sebanyak 6 orang dengan instrumen angket terkait aspek motivasi, kemudahan, kemenarikan, dan kemanfaatan yang mendapatkan skor rerata sebesar 83,667, dan pengguna pada uji lapangan produk utama sebanyak 30 orang dengan instrumen angket terkait aspek motivasi, kemudahan, kemenarikan, dan kemanfaatan yang mendapatkan skor rerata sebesar 81,8. Indikator yang digunakan adalah jika rentang skor rerata > 83,994 termasuk kategori sangat layak dan 67,998 < skor rerata ≤ 83,994 termasuk kategori layak.